The untold stories of women in historically disadvantaged communities, infected and/or affected by HIV/AIDS, about care and/or the lack of care - Muller, Julian C. (University of Pretoria, 2013)
Thesis (PhD (Practical Theology))--University of Pretoria, 2005.